Excess female mortality in Africa - Siwan Anderson; Debraj Ray (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
Relative to developed countries, there are far fewer women than men in parts of the developing world. Estimates suggest that more than 200 million women are demographically 'missing' worldwide. To explain the global 'missing women' phenomenon, research has mainly focused on excess female mortality in Asia. However, as emphasized in our earlier research, at least 30 per cent of the missing women are 'missing' from Africa. This paper employs a novel methodology to determine how the phenomenon of missing women is distributed across Africa. Moreover, it provides estimates of the extent of excess female mortality within different age groups and by disease category. The empirical results reiterate the importance of excess female mortality for women in Africa.
Keywords: D13; I15; J12; J13; J16; 330; missing women; mortality; gender; Africa; health